Letter from C. Wiegand to James Curtis Booth, June 12, 1856 - Wiegand, Conrad (1856)
C. Wiegand writes from the United States Mint Assay Office to obtain information regarding refining techniques from James Curtis Booth (1810-1888).
Keywords: Booth, James Curtis, 1810-1888; Metals--Refining; Assaying; United States Mint; Mint of the United States